Urgensi Penanggulangan Kemiskinan Berbasis Kearifan Lokal di Kabupaten Aceh Utara - Ferizaldi Ferizaldi (Jurnal Sosiologi USK (Media Pemikiran & Aplikasi), 2022)
The poverty rate in North Aceh District is still quite high, it was inversely proportional to the glory of the gas and oil industries in the past, so it once earned the nickname "petrodollar area." The government has been trying to overcome the spike in the poverty rate, but poverty is still increasing. This article aims to describe local wisdom as an aspect that can be used as part of a poverty alleviation strategy in North Aceh. This study uses a qualitative method. Data sources were obtained from interviews, observation, and documentation, then analyzed interactively. This study showed that the poverty alleviation efforts carried out by the North Aceh government are still partial and centralized. The cultural aspect, such as the community's local wisdom in accordance with Islamic values, is still not given enough attention. The realization of activities carried out so far are still focused on national programs from the central government, and efforts to collaborate and connect with local cultural aspects have not been made. Whereas local wisdom can be a part of a poverty alleviation mechanism because it has become a social norm and a valued asset in Acehnese society.AbstrakAngka kemiskinan di Kabupaten Aceh Utara masih cukup tinggi, berbanding terbalik dengan kejayaan industri migas di masa lalu, sehingga sempat mendapat julukan “daerah petrodolar”. Pemerintah telah berusaha mengatasi lonjakan angka kemiskinan, namun angka kemiskinan tetap saja meningkat. Artikel ini bertujuan untuk mendeskripsikan kearifan lokal sebagai salah satu aspek yang dapat dijadikan sebagai bagian dari strategi pengentasan kemiskinan di Aceh Utara. Penelitian ini menggunakan metode kualitatif. Sumber data diperoleh dari wawancara, observasi, dan dokumentasi, kemudian dianalisis secara interaktif. Kajian ini menunjukkan bahwa upaya pengentasan kemiskinan yang dilakukan pemerintah Aceh Utara masih bersifat parsial dan terpusat. Aspek budaya seperti kearifan lokal masyarakat yang sesuai dengan nilai-nilai Islam masih kurang diperhatikan. Realisasi kegiatan yang dilakukan selama ini masih terfokus pada program nasional dari pemerintah pusat, dan belum dilakukan upaya untuk berkolaborasi dan terkoneksi dengan aspek budaya lokal. Padahal kearifan lokal dapat menjadi bagian dari mekanisme pengentasan kemiskinan karena telah menjadi norma sosial dan aset berharga dalam masyarakat Aceh.